2016
DOI: 10.3897/zookeys.578.8052
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the Australian trans-Bass Strait millipede genus Pogonosternum (Carl, 1912) (Diplopoda, Polydesmida, Paradoxosomatidae) indicates multiple glacial refugia in southeastern Australia

Abstract: This study documents the first detailed phylogenetic analysis of an Australian paradoxosomatid millipede genus. Two mitochondrial genes (partial COI and 16S) as well as partial nuclear 28S rDNA were amplified and sequenced for 41 individuals of the southeastern Australian genus Pogonosternum Jeekel, 1965. The analysis indicates that five species groups of Pogonosternum occur across New South Wales, Victoria and Tasmania: Pogonosternum nigrovirgatum (Carl, 1912), Pogonosternum adrianae Jeekel, 1982, Pogonostern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Total genomic DNA was extracted using a Qiagen DNAeasy Blood & Tissue kit following the standard protocol with an incubation of tissue for 48h. Glom primer cocktail pairs (Decker 2016a, 2016b, Macek et al 2014) were used to sequence a 618 bp fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Primer pairs 28S D1a (Fw) and 28S D3b (Rv) (Dell’Ampio et al 2009) were used to amplify 1225 bp of the D2 fragment and adjacent areas of D1 and D3 on the nuclear 28S ribosomal RNA gene.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total genomic DNA was extracted using a Qiagen DNAeasy Blood & Tissue kit following the standard protocol with an incubation of tissue for 48h. Glom primer cocktail pairs (Decker 2016a, 2016b, Macek et al 2014) were used to sequence a 618 bp fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Primer pairs 28S D1a (Fw) and 28S D3b (Rv) (Dell’Ampio et al 2009) were used to amplify 1225 bp of the D2 fragment and adjacent areas of D1 and D3 on the nuclear 28S ribosomal RNA gene.…”
Section: Methodsmentioning
confidence: 99%
“…Primer pairs 16Sar (Fw) (5’-CGCCTGTTTAACAAAAACAT-3’) and 16Sbr (Rv) (5’-CCGGTCTGAACTCAGATCACGT-3’) (Simon et al 1994) were used to sequence a 566 bp fragment of the large-subunit ribosomal RNA (16S) gene. For PCR protocol and all primer sequences (COI, 16S, 28S) see Decker (2016a, 2016b). Fragments were sequenced in both directions by the BiK-F Laboratory Centre, Frankfurt, Germany.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogenetic analysis (Decker 2016a) showed that this species is very closely related to P. laetificum with low genetic distances between populations of the two species.…”
Section: Remarksmentioning
confidence: 96%
“…10), sometimes both forms present within one population, with male brushes ranging to legpair 7, except in Brisbane Ranges National Park to legpair 9. Pogonosternum coniferum is here made a synonym of P. nigrovirgatum due to the existence of these intermediate forms and the fact that P. coniferum clusters with P. nigrovirgatum in a phylogenetic analysis based on mitochondrial COI and 16S rDNA sequences (Decker 2016a). …”
Section: Remarksmentioning
confidence: 99%